Fraud Prevention and Internal Control in the Nigerian Banking System - Adetiloye, Kehinde Adekunle; Olokoyo, Felicia Omowunmi; Taiwo, Joseph Niyan (International Journal of Economics and Financial Issues, 2016)
Fraud and internal control issues dominate banking operations as concerns that impinge adversely on banks’ reputation for safety and performance. This paper examines the issues of internal control vis a vis fraud prevention in the banking industry, adopting both primary and secondary data. Primary data was used to test internal control while secondary data were employed to test fraud prevention. The main primary variables were separation of duties, monitoring, and staff qualifications while the main secondary variables are bank profit, regulation, technology and M2. In both cases regression techniques were adopted. The results show that internal control on its own is effective against fraud, but not all staffs are committed to it, while the secondary data is quite supportive of the primary data but more exemplifying in that M2, staff qualifications and technology were significant throughout the various dependent variables. It is also clear from the regressions that technological based fraud is significant. The paper recommends the continuation of the cashless policy of the Central Bank to reduce available cash and improvement in educated staff engagement to reduce fraud in the banking system. Keywords: Deposit Money Banks; Internal Control; Fraud Prevention; Regulation; Cashless Policy JEL Classifications: G21, G38